Prevocational Integrated Extended Rural Clinical Experience (PIERCE): cutting through the barriers to prevocational rural medical education - Dale Hanson; Eleanor Carey; Jane Harte; Deanne Bond; Dan Manahan; Patrick O'Connor (James Cook University, 2020)
Introduction: Despite an increase in the number of undergraduate training positions, Australia faces a critical shortage of medical practitioners in regional, rural and remote communities. Extended rural clinical placements have shown great utility in undergraduate medical curricula, increasing training capacity and providing comparable educational outcomes while promoting rural medicine as a career. The Prevocational Integrated Extended Rural Clinical Experience (PIERCE) was developed to increase the training capacity of the Queensland Rural Generalist Pathway (QRGP) and strengthen trainee commitment to rural practice by offering an authentic, extended 15-week rural term that provided an integrated experience in anaesthetics, obstetrics and gynaecology, and paediatrics, while meeting the requirements for satisfactory completion of prevocational rural generalist training. This study sought to evaluate whether trainees believed PIERCE and/or traditional regional hospital specialty placements achieved their learning objectives and to identify elements of the placements that contributed to, or were a barrier to, their realisation. Methods: This translational qualitative study explored the experiences and perceptions of QRGP trainees who undertook a PIERCE placement in three Queensland rural hospitals (Mareeba, Proserpine and Stanthorpe) in 2015, with a matched cohort of trainees who undertook regional hospital placements in anaesthetics, obstetrics and gynaecology, and paediatrics at a regional referral hospital (Cairns, Mackay and Toowoomba base hospitals). The study used a realist evaluation framework that investigates What works, for whom, in what circumstances, in what respects and why? Results: PIERCE provided an enjoyable and valued rural training experience that promoted trainee engagement with, and contribution to, a rural community of practice, reinforcing their commitment to a career in rural medicine. However, QRGP trainees did not accept that PIERCE could be a substitute for regional hospital experience in anaesthetics, obstetrics and gynaecology, and paediatrics. Rather, trainees thought PIERCE and regional hospital placements offered complementary experiences. PIERCE offered integrated, hands-on rural clinical experience in which trainees had more autonomy and responsibility. Regional hospital placements offered more traditional caseload learning experiences based on observation and the handing down of knowledge and skills by hospital-based supervisors. Conclusion: Both PIERCE and regional hospital placements provided opportunities and threats to the attainment of the curriculum objectives of the Australian Curriculum Framework for Junior Doctors, the Australian College of Rural and Remote Medicine and the Royal Australian College of General Practitioners Fellowship in Advanced Rural General Practice curricula. PIERCE trainees enjoyed the opportunity to experience rural medicine in a community setting, a broad caseload, hands-on proficiency, continuity of care and an authentic role as a valued member of the clinical team. This was reinforced by closer and more consistent clinical and educational interactions with their supervisors, and learning experiences that address key weaknesses identified in current hospital-based prevocational training. Successful achievement of prevocational curriculum objectives is contingent on strategic alignment of the curricula with supportive learning mechanisms focused by the learning context on the desired outcome, rural practice. This study adds weight to the growing consensus that rural community-based placements such as PIERCE are desirable components of prevocational training.